دور مكتبات الأطفال في عصر المعلومات - علي, أحمد (University of Eloued جامعة الوادي, 2010)
يشكل الأطفال الجزء الأكبر من المجتمعات التي نعيش فيها، وتمثل المادة العلمية التي يكتسبونها هي الأقل حظًا بالنسبة للمعلومات المنتشرة في هذا العصر، وفي مجمل تلك المواد لا تعطي الطفل الثقافة والعلوم اللازمة لإشباع حاجاته الثقافية، وخاصة أن المادة الثقافية منتشرة في هذا العصر عصر التقنية والمعلومات، عصر الشبكة المعلوماتية. تتناول الدراسة مكتبة الطفل في عصر المعلومات، والشروط الواجب توفرها فيها والإمكانيات الواجب إدراجها فيها حتى يستفيد منها الاستفادة المثلى، كما تناولت العديد من المفاهيم المتعلقة بعصر المعلومات والمكتبات بشكل عام. ABSTRACT: Children forms the big part of the society we lived in, but the scientific material earned is the small chance according to the information spread at this time, all these materials could not give the child culture and science he need to satisfy his cultural needed, specially the cultural material spread at this technology and information time as internet information. At this study I have been discussed child libraries at information time, and the conditions should be supplied at, and the abilities should be insert in, so the child could use it at the best way, and have discussed the definitions according the information time and libraries.
مقال بمجلة البحوث والدراسات
Keywords: مكتبات - أطفال - عصر المعلومات